Visualizing Research Trends on the Impact of STEM-Integrated Project-Based Learning Model on 21st-Century Skills Using VOSviewer and Harzing's Publish or Perish: A Systematic Literature Review - Wardana, Irfan Ihza; Sukaesih, Sri; Dewi, Novi Ratna (Universitas Negeri Semarang, 2024)
The 21st-century skills are essential component of curriculum frequently implemented in schools and universities to equip students for competition in the labor market. Integrating STEM (Science, Technology, Engineering, and Mathematics) into Project-Based Learning (PjBL) promotes active student engagement and interdisciplinary problem-solving to tackle complex issues. This article aims to provide research recommendations on how the STEM-integrated PjBL model affects students' 21st-century skills and to provide information on rarely-researched trends in this field. A Systematic Literature Review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, utilizing Harzing's Publish or Perish software, VOSviewer, and Google Scholar databases, focusing on thirty references published between 2019 and 2023. The findings indicated that the STEM-based PjBL approach significantly enhances students' 21st-century skills, including critical thinking, creativity, collaboration, communication, conceptual understanding, and problem-solving abilities, thereby preparing them to navigate complex global challenges. Effective implementation requires interdisciplinary teacher collaboration, technology integration, and supportive learning environments. However, the analysis highlights that the integration of STEM and PjBL has not been extensively associated with collaboration and communication skills, presenting a valuable opportunity for future research in this area.